Corrosion behaviour of Fe-25Cr alloy in wet CO2 gas at 650 °C: Effects of chloride deposits and Si+Mn alloying addition. (February 2022) - Cai, Yuchen; Nguyen, Thuan Dinh; Zhang, Jianqiang; Gleeson, Brian; Young, David J.
Abstract: A model ferritic Fe-25wt% Cr alloy exposed to an Ar-60CO2 -20H2 O gas mixture at 650 °C experienced rapid oxide scale growth and simultaneous internal carburization. When a deposit of NaCl-KCl was present on the alloy surface, it developed a more porous oxide scale and more extensive carburization. In the absence of salt, alloy additions of Si+Mn led to improved protection: slow oxide scaling and no carburization. In the presence of salt, this protection was much reduced. These effects are discussed in terms of oxide volatilisation and ferrite chromium concentration depletion by carburization. Highlights: Fe-25Cr alloy experienced breakaway oxidation and internal carburization in wet CO2 gas with and without chloride presence. The addition of Si and Mn led to improved protection which is more significant in the gas-only condition. The presence of chloride deposits changed the morphologies of oxides, forming more porous oxide products. The accelerated corrosion by chloride was attributed to oxide volatilisation and Cr depletion by carburization.